Prevalence and Antimicrobial Susceptibility of Methicillin-Resistant Staphylococcus aureus in an Egyptian University Hospital - Ahmed E. Taha; Mohammad F. Badr; Fikry E. El-Morsy; Enas Hammad (Journal of Pure and Applied Microbiology, 2019)
The relative high burden of morbidity and mortality caused by Staphylococcus aureus (SA) in healthcare and community settings is a major concern worldwide. It can cause invasive infections, sepsis and deaths. Despite progress in methicillin-resistant S. aureus (MRSA) prevention in healthcare settings, there is a critical need for assessment of the problem in both healthcare and community settings. This study was conducted for examining the prevalence, risk factors and antimicrobial susceptibility of MRSA in Mansoura University Hospitals (MUHs), Egypt. Samples were collected from patients in MUHs with clinically suspected nosocomial infections. MRSA isolates were identified by the standard bacteriological methods, biochemical reactions and disc diffusion method as recommended by the Clinical & Laboratory Standards Institute (CLSI), then confirmed by MecA gene PCR. A total of 2006 isolates was obtained. SA (32%) was the most frequently isolated pathogen. MRSA (130 isolates) represented 20% of SA and 6.48 % of all isolates. The mecA PCR identified SA as MRSA in 99.2% of cases. MRSA was isolated with another organism (mostly Gram-negative bacilli) from 40.8% of cases while 59.2% of MRSA was isolated alone. The most important reported risk factors for MRSA infections were prolonged hospital stays, recent antibiotic therapy, ICU admission, indwelling devices and presence of surgical sutures. MRSA was resistant to many antibiotics but sensitive to vancomycin in 99.2% of cases. Minimizing exposure to the risk factors with rapid diagnosis of MRSA infections are essential for early initiation of appropriate antibiotic treatment and limitation of the non-optimal use of glycopeptides and deaths.